2011
DOI: 10.2466/02.09.pr0.109.6.907-920
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Brief Measure of Social Self-Efficacy among U.S. Adolescents

Abstract: Preliminary data were collected to evaluate the performance of a social self-efficacy measure among 4,061 public high school adolescents. Principal-axis factor analysis was followed by a 4-way between-groups analysis of variance (ANOVA) to test for differences in the Total score means on selected demographic estimates and their interactions. Relations between the Total score and selected risk behaviors were examined through a series of one-way ANOVAs and the Tukey HSD test. Factor analysis results suggested a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 23 publications
5
30
2
Order By: Relevance
“…Consistent with prior studies, single-factor structures emerge across our full sample. Overall, our data yield generally higher mean ASE and SSE scores than those reported by in prior studies (Suldo & Shaffer, 2007;Zullig et al, 2011). Like Zullig et al's study, we find higher SSE scores for females as compared to males and for White youth as compared to other ethnic groups.…”
Section: Discussion and Applications To Practicesupporting
confidence: 63%
See 1 more Smart Citation
“…Consistent with prior studies, single-factor structures emerge across our full sample. Overall, our data yield generally higher mean ASE and SSE scores than those reported by in prior studies (Suldo & Shaffer, 2007;Zullig et al, 2011). Like Zullig et al's study, we find higher SSE scores for females as compared to males and for White youth as compared to other ethnic groups.…”
Section: Discussion and Applications To Practicesupporting
confidence: 63%
“…Social forms of self-efficacy predict adolescents' ability to face social challenges. Zullig, Teoli, and Valois (2011) found significant mean differences, with modest effect sizes, in SSE between youth who reported fighting, avoiding school, and being victimized. They also found that White students had significantly higher SSE than African American and Asian students, with small effect sizes.…”
mentioning
confidence: 83%
“…The survey examined social psychological variables including social self-efficacy, collective self-esteem, and need to belong. Previous research Social Media & Collective Action 12 guided the measurement of these concepts (e.g., Baker, 2009;Gangadharbatla, 2008;Harwood, 1999;Hlebec, Manfreda and Vehovar, 2006;Ledbetter, et al, 2011;Pelling and White, 2009;Valkenburg and Peter, 2008;Zullig, Teoli and Valois, 2011). Prior questions were adapted to make them more relevant to this study.…”
Section: Measured Variablesmentioning
confidence: 99%
“…The eight-item measure of SSE used was adapted from Muris (2002) and modified for use in this population. Specifically, five scale items were modified: ''How (Muris, 2001(Muris, , 2002Zullig et al, 2011).…”
Section: Ssementioning
confidence: 99%